Cerita Anak berbasis Digital sebagai Upaya Orang Tua dalam Perkembangan Bahasa, Intelektual dan Moral Anak - Yanti, Dewi; Hotimah, Wiwin Husnul; Zulfikar, Zulfikar; Putri, Nafi’ Kharisma; Oktaviani, Diah Ayu; Sidik, Alpin Nur (Prodi Ekonomi Syariah Universitas Pamulang, 2023)
Various cases of child development are rife in society. Cases of child development such as language, intellect, and morals deserve important attention. The lack of acquisition of language and literacy that is appropriate for their age is one of the inhibiting factors in children's development that has an impact on their language, psychology, and morals. The stuttering of technology and the communication media experienced by parents are also other factors. It was on this case basis that the PKM team conducted counseling entitled